2018
DOI: 10.5851/kosfa.2018.e67
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Lactococcus lactis Strain Producing Anti-staphylococcal Bacteriocin

Abstract: Bacteriocin is ribosomally synthesized by bacteria and inhibits closely related species. In this study we aimed at isolating lactic acid bacteria producing bacteriocin presenting anti-staphylococcal activity. A Lactococcus lactis strain was isolated from kimchi for the purpose and identified by 16S rRNA gene sequencing. As preliminary tests, optimal culture conditions, stabilities against heat, solvents, and enzymes treatments, and type of action (bacteriostatic or bactericidal) of the bacteriocin were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Furthermore, the TBC count increased with the increased ratio of LAB. These results were supported by previous findings of (Park et al, 2018; Yang and Moon, 2018) reported that administration of LAB in minced beef inhibiting the growth of bacteria.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, the TBC count increased with the increased ratio of LAB. These results were supported by previous findings of (Park et al, 2018; Yang and Moon, 2018) reported that administration of LAB in minced beef inhibiting the growth of bacteria.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, L. lactis has been found to change the virulence of S. aureus by downregulating its accessory gene regulator (agr) system (49). L. lactis has also been found to produce S. aureus inhibiting biocins (50). Additional inhibiting methods might consist of a quorum-quenching effect, as it has been shown between Bacillus subtilis and S. aureus in humans (51).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, 73 strains of S. aureus , including MRSA strains, were found to be susceptible against recombinant SAP8 endolysin, including S. aureus KCTC 3881, which demonstrated that recombinant SAP8 is not strain-specific [ 16 ]. In our previous study, we tested crude nisin from L. lactis strain against several S. aureus strains and found strongest activity of nisin against S. aureus KCTC 3881, chosen as a model strain in this study [ 19 ]. To test activities of recombinant SAP8 endolysin and nisin, S. aureus KCTC 3881 strain was cultured in MRS broth (BD, Sparks, MD, USA) at 37 ℃ for 12 h. To measure CFU/mL, 10 times serial dilutions of culture was made, then we poured 10 µL of each dilution on MRS agar plate in triplicate form.…”
Section: Methodsmentioning
confidence: 99%